2004
DOI: 10.1177/021849230401200213
|View full text |Cite
|
Sign up to set email alerts
|

Tricuspid Valve Replacement: Bioprosthetic or Mechanical Valve?

Abstract: Significant morbidity and mortality is associated with tricuspid valve replacement, and controversy still exists as to the ideal prosthesis in this position. This study aimed to identify the risk factors for low cardiac output and mortality, and whether bioprosthetic or mechanical valves perform better in the tricuspid position. Results of 121 tricuspid valve replacements in 104 patients between January 1966 and December 2002 were reviewed. Most patients were in New York Heart Association functional class III … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Based on our literature research strategy, 26 studies were identified, all of which were retrospective. Among these studies, the series of Rizzoli and colleagues, van Nooten and colleagues, Do and colleagues, and Hwang and colleagues were replicated in two different papers and the duplicated data were excluded to avoid estimation bias .…”
Section: Resultsmentioning
confidence: 99%
“…Based on our literature research strategy, 26 studies were identified, all of which were retrospective. Among these studies, the series of Rizzoli and colleagues, van Nooten and colleagues, Do and colleagues, and Hwang and colleagues were replicated in two different papers and the duplicated data were excluded to avoid estimation bias .…”
Section: Resultsmentioning
confidence: 99%
“…TVR is associated with high morbidity and mortality. The operative mortality for TVR was 14.3% to 24.5% 10‐13 . The late survival rate is also suboptimal with a 5‐year and 10‐year survival at 56% to 70% and 45% to 52%, respectively 10,14‐16 .…”
Section: Discussionmentioning
confidence: 99%
“…The operative mortality for TVR was 14.3% to 24.5%. [10][11][12][13] The late survival rate is also suboptimal with a 5-year and 10-year survival at 56% to 70% and 45% to 52%, respectively. 10,[14][15][16] TVP is superior to TVR with lower hospital mortality, fewer thromboembolic complications, and longer survival.…”
Section: Methodsmentioning
confidence: 99%
“…9 Despite this controversy, the survival is probably similar for mechanical and bioprostheses. 8,10,11 Overall, the tricuspid valve is more prone to thrombosis and pannus formation, irrespective of whether a bioprosthesis or a mechanical valve is used. Pannus formation occurs mostly on the ventricular side and has a 35% incidence at five years' follow-up.…”
Section: Tricuspid Diseasementioning
confidence: 99%